Effects of salinity on three mandarin cultivars grafted on two different rootstocks - Velásquez Ochoa, Edwin Ricardo; Burga, C.; Vargas, L. (Universidad Nacional Agraria La Molina, 2022)
Citrus, one of the most important fruit crops in the world and also they are sensitive to salt stress. The negative effects of stresses often lead to reductions in fruit yield and quality. To assess the effects of salinity on some growth traits, a greenhouse test was performed with the cultivars ‘Mihowase’, ‘Primosole’ and ‘W. Murcott’ as grafted on ‘Cleopatra’ and ‘Swingle citrumelo’ as rootstocks. The experiment was conducted at the Agrarian Experimental Station of National Institution for Agricultural Innovation in Donoso-Huaral, ubicated 90 km north of Lima. The plants were irrigated with water plus NaCl with an Electrical Conductivity of 0.5 or 4.5 dS/m as salt stress. The variables under evaluation were leave losses, fresh and dry weight of stem, leaves and roots as well as relative water content in the plants. The results showed that the rootstocks ‘Cleopatra’ was more tolerant than ‘Swingle citrumelo’. The cultivars used as scions affected both rootstocks in all the evaluated traits being more notorious in the amount of feeding roots. Selection of mandarin trees for production shout take in consideration the combination scion/rootstock.